Microarray Analysis of Developing Arabidopsis Seeds - Girke, Thomas (American Society of Plant Physiologists, 2000)
To provide a broad analysis of gene expression in developing Arabidopsis seeds, microarrays have been produced that display approximately 2,600 seed-expressed genes. DNA for genes spotted on the arrays were selected from >10,000 clones partially sequenced from a cDNA library of developing seeds. Based on a series of controls, sensitivity of the arrays was estimated at one to two copies of mRNA per cell and cross hybridization was estimated to occur if closely related genes have >70% to 80% sequence identity. These arrays have been hybridized in a series of experiments with probes derived from seeds, leaves, and roots of Arabidopsis. Analysis of expression ratios between the different tissues has allowed the tissue-specific expression patterns of many hundreds of genes to be described for the first time. Approximately 25% of the 2,600 genes were expressed at ratios ≥ 2-fold higher in seeds than leaves or roots and 10% at ratios ≥ 10. Included in this list are a large number of proteins of unknown function, and potential regulatory factors such as protein kinases, phosphatases, and transcription factors. The Arabidopsis arrays were also found to be useful for transcriptional profiling of mRNA isolated from developing oilseed rape (Brassica napus) seeds and expression patterns correlated well between the two species.